(untitled) (Journal of the College of Basic Education, 2022)
The subject of chemistry - like all other scientific subjects - is accused of stagnation and the complexity of its topics, and its branches in many cases so that it needs more explanation and detail to clarify its idea, and this may not be available when presented by its teachers; Due to the lack of time or the increase in the number of students, especially in our overcrowded schools, which makes it difficult for them to deal with all its sections; Because of their preoccupation with the issue of taking into account individual differences, as well as their preoccupation with controlling their classroom environment, and therefore these issues may negatively affect the achievement of their students. Through the researcher’s modest experience in teaching this subject and his meeting with a group of his colleagues in the specialty, it was shown that despite everything that was raised about it, the level of what their learners achieve is very low on the level of achievement; This is because they follow ways and methods of presenting their material, which were characterized by rigidity and excessive stereotyping, so the researcher resorted to reviewing the educational literature to address these problems, and ward off accusations about his subject that he teaches. And the closed) had an effect on increasing the level of achievement of fifth grade students in applied chemistry?!